Elbow Dislocation Associated with Severely Displaced Radial Neck Fracture and Ulnar Diaphyseal Fracture in an 11-Year-Old Girl - A Very Rare Case Report - Louis Biernaux; Valentina Maestri; Manon Deguée; Pierre-Louis Docquier (Journal of Orthopaedic Case Reports)
Introduction: Association of elbow dislocation, radial neck fracture (RNF), and ulnar shaft fracture has not been reported previously in the pediatric population. Case Report: This 11-year-old girl fell from her height. She presented a severely displaced RNF, a greenstick fracture of the proximal ulnar shaft, and a posterior elbow dislocation. Conclusion: This article describes a very rare case, shows a possible treatment, and presents the follow-up with a final good result.